Komunikasi Persuasif Penyuluh Agama Dalam Mengubah Perilaku Beragama Masyarakat Desa Kale Lantang Kabupaten Takalar Sulawesi Selatan - A. Rivai Beta (Asosiasi Dosen Muda Indonesia, 2025)
This study aimed to describe the persuasive communication of religious counselors in changing the community’s religious behavior in Kale Lantang Village, Takalar Regency, South Sulawesi. The research used a qualitative approach focusing on village residents and the counselors assigned to the area. Data were collected through interviews and analyzed using data triangulation to strengthen credibility. The findings showed that the counselors applied DeVito’s concept of persuasive communication. At the selective exposure stage, the South Polongbangkeng Office of Religious Affairs (KUA) placed counselors by considering location suitability and their understanding of the local context. In terms of audience participation, counselors conducted dialogues and organized religious gatherings (majelis) at the mosque, but community involvement remained low. Regarding the inoculation principle, counselors tended to use a reversed pattern by responding to resistance after it appeared rather than preparing preventive messages beforehand. Major obstacles included the government’s intention to maintain certain practices and the community’s strong adherence to ancestral traditions. Therefore, the study recommended training for counselors and sustained collaboration with village authorities and community leaders to enhance behavioral change efforts.